Study of Slurry Flow Behaviour Of Multi-Sized Particulate Ash Slurry - Madan, Komal (My University, 2013)
Transportation of fly ash to the ash ponds from thermal power stations was disposed by slurry pipeline. Both the power plant i.e. Guru Nanak Dev Thermal power Plant, Bathinda and Rajiv Gandhi Thermal Power Plant, Hissar are transporting fly ash at low concentration which leads to more power requirement and water supply. Also reduce the life of pipeline due to excessive pipeline erosion wear. Present work is aim to investigate the various physical as well as chemical properties such as Particle Size distribution, pH, Settling, Zeta Potential, SEM, EDX, Specific Gravity of two fly ash sample collected from Guru Nanak Dev Thermal Power Plant, Bathinda and Rajiv Gandhi Thermal Power Plant, Hissar. Rheology of both sieved as well as unsieved sample is studied at concentration varying from 30%-60% and particle size from 53-106 microns with and without additive (Sodium Lauryl Ether Sulphate). The slurry exhibit Newtonian behaviour till 40% for particle size below 53 and 53-75 microns and Non – Newtonian behaviour at 50% concentration. Addition of surfactant reduces the viscosity and makes the fly ash particle water borne at pH 6. Using rheological data, pressure drop has been calculated with the help of computer program on various efflux concentrations (40%, 50%, 60%) and flow velocity (1, 1.5, 2, 2.5, 3) m/s. The pressure drop in pipeline increases with increase in velocity. For the calculation of pressure drop in the slurry pipeline a computer program using C has been gene
ME, MED
Keywords: Fly Ash; Particle Size distribution; Rheology